Novel Combination of Surface Markers for the Reliable and Comprehensive Identification of Human Thymic Epithelial Cells by Flow Cytometry: Quantitation and Transcriptional Characterization of Thymic Stroma in a Pediatric Cohort - Haunerdinger, Veronika; Moccia, Maria Domenica; Opitz, Lennart; Vavassori, Stefano; Dave, Hitendu; Hauri-Hohl, Mathias M. (Frontiers in Immunology, 2021)
Thymic epithelial cells (TECs) are essential in supporting the development of mature T cells from hematopoietic progenitor cells and facilitate their lineage-commitment, proliferation, T-cell receptor repertoire selection and maturation. While animal model systems have greatly aided in elucidating the contribution of stromal cells to these intricate processes, human tissue has been more difficult to study, partly due to a lack of suitable surface markers comprehensively defining human TECs. Here, we conducted a flow cytometry based surface marker screen to reliably identify and quantify human TECs and delineate medullary from cortical subsets. These findings were validated by transcriptomic and histologic means. The combination of EpCAM, podoplanin (pdpn), CD49f and CD200 comprehensively identified human TECs and not only allowed their reliable distinction in medullary and cortical subsets but also their detailed quantitation. Transcriptomic profiling of each subset in comparison to fibroblasts and endothelial cells confirmed the identity of the different stromal cell subsets sorted according to the proposed strategy. Our dataset not only demonstrated transcriptional similarities between TEC and cells of mesenchymal origin but furthermore revealed a subset-specific distribution of a specific set of extracellular matrix-related genes in TECs. This indicates that TECs significantly contribute to the distinct compartmentalization – and thus function – of the human thymus. We applied the strategy to quantify TEC subsets in 31 immunologically healthy children, which revealed sex-specific differences of TEC composition early in life. As the distribution of mature CD4- or CD8-single-positive thymocytes was correspondingly altered, the composition of the thymic epithelial compartment may directly impact on the CD4-CD8-lineage choice of thymocytes. We prove that the plain, reliable strategy proposed here to comprehensively identify human TEC subpopulations by flow cytometry based on surface marker expression is suitable to determine their frequency and phenotype in health and disease and allows sorting of live cells for downstream analysis. Its use reaches from a reliable diagnostic tool for thymic biopsies to improved phenotypic characterization of thymic grafts intended for therapeutic use.